Lipid peroxide and transition metals are required for the toxicity of oxidized low density lipoprotein to cultured endothelial cells - Kuzuya, M; Naito, M; Funaki, C; Hayashi, T; Asai, K; Kuzuya, F (Biochimica et biophysica acta, 1991)
The toxicity of oxidized low density lipoprotein (Ox-LDL) to cultured vascular endothelial cells was investigated. The modification of low density lipoprotein (LDL) by copper led to the production of thiobarbituric acid-reacting substance (TBARS) and lipid hydroperoxide (LPO). TBARS was distributed not only in lipoprotein, but also in the aqueous phase, whereas LPO was observed only in the lipoprotein particle. During the incubation of LDL with copper, the copper bound to lipoprotein and formed a complex. The toxicity of products resulting from the oxidation of LDL to endothelial cells was recognized in Ox-LDL particles, not in the aqueous phase. Following dialysis of Ox-LDL against EDTA, copper which had bound to the Ox-LDL particle was released and the toxicity of Ox-LDL disappeared. The addition of copper to the dialyzed Ox-LDL restored the cytotoxicity. To a lesser extent this effect was also observed with the addition of iron. A study of the time-course of LDL oxidation showed that the toxicity of Ox-LDL depends upon the level of LPO, not upon the content of TBARS, the extent of negative charge or the protein adduct of aldehydes. These results demonstrate that transition metal is required for Ox-LDL toxicity and that the toxic moiety of the products resulting from LDL oxidation is LPO associated with the Ox-LDL particle.